Body Composition and Bone Mineral Density in Patients with Spondyloarthritis: A Case-Control Study - Nguyen, Hoang Thanh Van; Nguyen, Dinh Huan (Tạp chí Y Dược Huế, 2026)
Objectives: This study aimed to investigate the relationship between bone mineral density (BMD) and various body composition parameters in Vietnamese patients with SpA. Methods: A case-control study was conducted at Hue University of Medicine and Pharmacy University Hospital, Vietnam, involving 43 patients with SpA and 71 age-, sex-, and BMI-matched healthy controls. Dual-energy X-ray absorptiometry (DXA) was used to assess body composition, measuring BMD and Z-scores at the lumbar spine, femoral neck, and total hip. Additional parameters included muscle mass index (appendicular skeletal muscle mass (ASM), appendicular skeletal muscle mass index (ASMI), body fat percentage (BF%), and fat mass index (FMI). Multivariable linear regression models were used to analyze the associations between BMD and body composition variables, with mean differences and 95% confidence intervals calculated. Results: SpA patients had significantly reduced BMD in the lumbar spine and total hip compared to the healthy control group. Furthermore, significant positive correlations were observed between femoral neck BMD and both ASM (r=0.304, p=0.047) and ASMI (r=0.319, p=0.037), as well as between total hip BMD and ASMI (r=0.307, p=0.045). Conclusions: The findings highlight the importance of monitoring BMD in patients with SpA due to the observed bone loss. Further research is warranted to fully elucidate the complex interplay between inflammation, body composition, and bone health in SpA.